Withstanding cold nights at high elevation: thermal strategy of Atractus crassicaudatus, a nocturnal tropical snake endemic to the eastern Andes of Colombia - R. Felipe Paternina-Cruz; Martha L. Calderón-Espinosa (Revista Mexicana de Biodiversidad)
Thermoregulation in highland tropical environments imposes physiological challenges for reptiles. The interaction between individual thermal requirements with external thermal conditions in these environments remains mostly unknown. We examined the thermal strategy of the nocturnal snake Atractus crassicaudatus (Duméril, Bibron, and Duméril, 1854) in the highlands of the northern Andes. We depicted the relationship between the snake´s body temperatures on the field and under experimental conditions, with operative temperatures during 2 climatic seasons. Additionaly, we compared selected temperatures (Tsel) during the day (photophase) and night (scotophase). Individuals selected different body temperatures under dry (Tsel = 19.53-21.30 °C) and rainy (Tsel = 17.27-19.23 °C) seasons, they actively thermoregulate during the dry season, and they are thermoconformers during the rainy season. Their preference for rocky-shelters in open to semi-open habitats, and the seasonal adjustment of Tsel, suggest thigmothermy with plastic thermal physiology. Individuals select a similar range of temperatures during photophase and scotophase, then, thermoregulatory behavior might occur even during the “inactivity phase.” This nocturnal snake copes with the circadian and seasonal variation of environmental thermal quality through behavior and physiological adjustments.